Excess molar heat capacities as function of composition of binary solutions - V. M. Raeva (Тонкие химические технологии, 2009)
The concentration dependences of excess molar heat capacities of binary solutions is investigated. The projection of the systems behavior in terms of limited information is considered. The necessity of account of these excess thermodynamic function at the calculation of distillation is discussed.